2019
DOI: 10.1007/s10761-019-00511-0
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Contact: Tradition and Innovation in Australian Contact Rock Art

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media, LLC, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to selfarchive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…We argue that contact rock art was used as a tool by Aboriginal communities to communicate cross-cultural experiences and empower community members to navigate threats and engage with new opportunities (e.g. Frieman and May 2020). As argued elsewhere, watercraft dominate the introduced subject matter of rock art made during the last 500 years in northwest Arnhem Land (e.g.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We argue that contact rock art was used as a tool by Aboriginal communities to communicate cross-cultural experiences and empower community members to navigate threats and engage with new opportunities (e.g. Frieman and May 2020). As argued elsewhere, watercraft dominate the introduced subject matter of rock art made during the last 500 years in northwest Arnhem Land (e.g.…”
Section: Introductionmentioning
confidence: 80%
“…Many hundreds of paintings were produced at Djulirri afterwards, including introduced watercraft, aircraft, European figures, a bicycle, a wagon, firearms, whaling gun, fighters wearing boxing gloves, letters from the English Alphabet, but also traditional subject matter such as depictions of Ngalyod (the Rainbow Serpent), kangaroos, and emus depicted in x-ray form, and more (e.g. Frieman and May 2020;May et al 2010;Figure 7). Other examples of sailing vessels were documented across the Wellington Range but in small numbers.…”
Section: Evidence In the Rock Artmentioning
confidence: 99%
“…As discussed earlier, rock art has the remarkable ability not only to reflect periods of stress within and between different societies but also to play an active role in assisting these groups in navigating these experiences (e.g. Frieman & May 2019). It should follow that sudden, obvious shifts in style evidenced in the archaeological record may be indicating such episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Chaloupka 1993). In fact, as recent research on contact rock art has shown (see Goldhahn & May 2019 for an overview) and as argued by Frieman and May (2019), Australian historical-period rock art reveals a dynamic, socially embedded series of practices which allowed new ideas, new materials and new ways of seeing the world to be examined, interrogated and selectively adopted into preexisting social structures and practices.…”
Section: Innovation In Rock Artmentioning
confidence: 99%
See 1 more Smart Citation